The impact of private sector credit on economic growth in Nigeria - Ganiyu B. A. Amoo; Matthew I. Eboreime; Yusuf Adamu; Maximillian C. Belonwu (CBN Journal of Applied Statistics, 2017)
The paper determines empirically the local conditions and policy environment that influence the absorptive capacity of credit in the Nigerian economy for the period 1993:Q1 to 2013:Q4 using fully modified least squares. Findings show that credit is growth-enhancing, even when trade openness, monetary policy, investment climate and infrastructure are low. Also, the composite local condition index analysis revealed that private sector credit increased economic growth when domestic or local conditions were favourable and the absorptive capacity of the domestic economy for credit was estimated at 29% of the GDP in 2013. These results suggest that there is ample room for growthenhancing credit expansion in Nigeria.
Keywords: A10; C10; C50; C51; 330; Absorptive Capacity; Credit; Fully Modified Least Squares Real economy